Perspectives on rural tourism geographies : case studies from developed nations on the exotic, the fringe and the boring bits in between / Rhonda L Koster, Doris A Carson Editors - Carson, Doris A Editors
This book examines rural tourism across three different contexts, acknowledging the complexity of rural places. It applies a systematic comparative framework across nine case studies from Australia, Canada and Sweden. The case studies address the uniqueness of different rural spaces, while the framework incorporates many theoretical aspects from human geography including spatial, historic, institutional, demographic, socio-economic and network perspectives. In the course of applying this comparative case study framework, the book identifies numerous implications for planning and policy in rural settings.